PENGARUH SUHU DAN UKURAN INANG TERHADAP BIOLOGI Trichogramma sp. PARASITOID TELUR PADA Cricula trifenestrata - ELLYDA ABAS WIKARDI; TOTO DJUWARSO; TYASNING N.; O. N. RISANTI (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
The experiment was conducted to study the effect of temperature and host size on the growth and development of Trichogramma sp., a species of parasitoid which attacks Cricula trfenestrata s eggs. The experiment was carried oul in the Pesl laboratory, Dalillro, Bogor. with relative humidity ranged between 60-80%. temperature ranged.between 23-25°C, 26-28°C, and 29-3 l